Hydrocarbon accumulation characteristics and main controlling factors of major salt-bearing basins in Central Asia - Li LIU; Kaixun ZHANG; Gang YU; Linjun YU; Haihua QIU; Yan ZHOU; Beiqi GE; Bakhtier NURTAEV; Shukhrat SHUKUROV (Shiyou shiyan dizhi)
The Amu Darya Basin and the Pre-Caspian Basin in Central Asia hold enormous hydrocarbon resource potential and are the most representative salt-bearing basins in the region. Based on the latest petroleum geological data, this study systematically compares the structural and sedimentary evolution, petroleum geological characteristics, and hydrocarbon distribution patterns of the basins. The main factors controlling hydrocarbon distribution in salt-bearing basins are thoroughly analyzed to deepen the understanding of regional hydrocarbon accumulation patterns in Central Asia. Since the Amu Darya Basin and the Pre-Caspian Basin are oil and gas-rich basins formed under different geological backgrounds, there are obvious differences in the tectonic evolution process, sedimentary strata and oil and gas geological characteristics of the two; however, the pre-salt basins have developed high-quality source rocks formed in the same rift period and depression period, with the characteristics of huge thickness, high organic matter abundance and high degree of thermal evolution. The extensive development of salt-bearing strata in the Amu Darya Basin and the Pre-Caspian Basin controls the spatial and temporal distribution of hydrocarbons. This salt-bearing system divides the basins into two hydrocarbon accumulation systems: sub-salt and supra-salt rock sequences. Hydrocarbons are mainly concentrated in the sub-salt Callovian to Oxfordian carbonate reservoirs in the Amu Darya Basin and in the sub-salt Carboniferous to Lower Permian carbonate reservoirs in the Pre-Caspian Basin. Gypsum-salt cap rocks exhibit excellent sealing properties and, in conjunction with favorable reservoir facies in the structural positions of the paleo-uplift of the sub-salt rock sequences, provide optimal conditions for forming large oil and gas fields. Additionally, salt windows induced by deep faults, gypsum-salt pinch-out zones, and salt tectonic activities facilitate vertical migration of hydrocarbons in sub-salt source rocks, playing a crucial role in large-scale hydrocarbon accumulation in supra-salt rock sequences.